Note - Shoreditch Immediate warrants out for arrest, 11 May 1926 (Shoreditch)
1926-05-11 "Note - Shoreditch Immediate warrants out for arrest, 11 May 1926" [g0231001.jpg], 11 May 1926 Local Organisation